DROMOLOGICAL SPEED AND ITS RELATIONSHIP TO DEMOCRACY AND HUMAN RIGHTS. - Dua, Mikhael (Prajñā Vihāra: Journal of Philosophy & Religion)
Technology does not only help humans to overcome natural challenges, but also has a dromological function in terms of channelling, communicating, connecting goods, information and messages, anonymous masses, and the needs from one pole to another, from one region to another, and even from one organ to another. In treating this phenomenon, Paul Virilio is fascinated by the accident which is assessed as value and danger of technologies. This article, then, aims to deal with the problem of dromological technology and its ethical implications for democracy and human rights.